Urban textile mills : conservation and conversion - Oevermann, Heike (Berlin : Wissenschaft Verlag, 2021)
Cover -- Titelei -- Impressum -- Contents -- Acknowledgments -- Urban Textile Mills: Conservation and Conversion -- Cities, industrialization, and urban textile mills -- General typology -- Inventory, conservation, and the typological approach -- Industrial heritage: diverse and global -- Reuse, conversion, and good practice -- Textile Cities and their Mills -- Pioneers and flagship projects in England -- Continental Europe: cities, extensions, and ongoing production -- Fractures and discontinuities -- The urban figuration of the industrial complexes -- Urban Industrial Typology and Spatial Structures of Historic Textile Mills -- Urban industrial typology -- From early block structures to urban blocks in transition -- Compositions: flagships and giants -- Additive structures, continuous changes, and early reuses -- The 20th century production halls -- Understanding the past transformations of the urban spatial structures -- Conservation and Conversion -- Heritage listing, conservation, and conversion -- Discussing good practice and further perspectives -- Colour plates -- Information on graphics -- Primary Sources -- Bibliography -- Index -- Illustration Credits -- The Author -- Cover II.
Keywords: Textile factories-Conservation and restoration-Europe.; Textile factories-Remodeling for other use-Europe.